2005
DOI: 10.1002/j.0022-0337.2005.69.10.tb04017.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endodontic Treatments Performed by Students in a Brazilian Dental School

Abstract: The aims of this study were to evaluate the clinical outcomes of root canal treatments performed by final-year students in the Dental School of Piracicaba, State University of Campinas, SP, Brazil, during the year 2000 and to evaluate the success rate of these treatments at follow-ups conducted one and three years later (2001-03). All 579 endodontic treatments performed by final-year students were selected for this investigation. Detailed personal and dental history was obtained from the patient's records. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
1
18
0
8
Order By: Relevance
“…These findings demonstrate satisfactory technical performance of the undergraduates, corroborating previous results reported at other dental schools. 4,5 Nevertheless, using criteria similar those adopted herein, several studies 6,10 have shown a poor quality of endodontic fillings performed by undergraduate dental students.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings demonstrate satisfactory technical performance of the undergraduates, corroborating previous results reported at other dental schools. 4,5 Nevertheless, using criteria similar those adopted herein, several studies 6,10 have shown a poor quality of endodontic fillings performed by undergraduate dental students.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the clinical results of this study, it can be assumed that the quality rating of the endodontic fillings was high, which is in agreement with previous investigations. 4,5,16 However, there are discrepancies as regards the results found by Eckerbom, 11 whose rates of inadequate fillings ranged from 54 to 62%. This discrepancy can possibly be explained by the fact that the above-mentioned studies evaluated the treatment performed by students under supervised conditions, whereas the others represent general practice.…”
Section: Ijedsmentioning
confidence: 86%
See 1 more Smart Citation
“…The results of this study were consistent with the research conducted by Quadros et al conducted a clinical and radiographic evaluation of root canal treatment carried out by final-level students of the Dental School of Piracicaba found that the success rate of root canal treatment evaluated ranged from 83% to 96% depending on pulp status before treatment. Pulp status before treatment shows the presence of pain, swelling, sinus tract, radiographic examination of periodontal ligaments occurs (6).…”
Section: Discusionmentioning
confidence: 99%
“…3 Some authors have suggested that this gap between research and clinical practice probably reflects the fact that, very often, manual techniques continue to be taught at some dental undergraduate programs. 4 Paradoxically, the well-known limitations of stainless steel hand endodontic instruments may contribute to the technical difficulties faced by students in the academic setting 5 and negatively impact their success rate in treating root canals during their practice both as students 6 and also after graduation 7 .…”
Section: Introductionmentioning
confidence: 99%